Evolutionarily distant pathogens require the Arabidopsis phytosulfokine signalling pathway to establish disease. (9th November 2015) - Rodiuc, Natalia; Barlet, Xavier; Hok, Sophie; Perfus‐Barbeoch, Laetitia; Allasia, Valérie; Engler, Gilbert; Séassau, Aurélie; Marteu, Nathalie; de Almeida‐Engler, Janice; Panabières, Franck; Abad, Pierre; Kemmerling, Birgit; et al.
Abstract: Secreted peptides and their specific receptors frequently orchestrate cell‐to‐cell communication in plants. Phytosulfokines (PSKs) are secreted tyrosine‐sulphated peptide hormones, which trigger cellular dedifferentiation and redifferentiation upon binding to their membrane receptor. Biotrophic plant pathogens frequently trigger the differentiation of host cells into specialized feeding structures, which are essential for successful infection. We found that oomycete and nematode infections were characterized by the tissue‐specific transcriptional regulation of genes encoding Arabidopsis PSKs and the PSK receptor 1 (PSKR1). Subcellular analysis of PSKR1 distribution showed that the plasma membrane‐bound receptor internalizes after binding of PSK‐α. Arabidopsis pskr1 knockout mutants were impaired in their susceptibility to downy mildew infection. Impaired disease susceptibility depends on functional salicylic acid (SA) signalling, but not on the massive up‐regulation of SA‐associated defence‐related genes. Knockout pskr1 mutants also displayed a major impairment of root‐knot nematode reproduction. In the absence of functional PSKR1, giant cells arrested their development and failed to fully differentiate. Our findings indicate that the observed restriction of PSK signalling to cells surrounding giant cells contributes to the isotropic growth and maturation of nematode feeding sites. Taken together, our data suggest that PSK signalling in Arabidopsis promotes the differentiation of host cells into specialized feeding cells. Summary Statement: Secreted peptides frequently determine plant development and the interaction with the environment. We analysed the role of tyrosine‐sulphated phytosulfokines (PSKs) for the interaction of Arabidopsis thaliana with leaf and root pathogens, including an oomycete, a bacterium and a root‐knot nematode. Functional analyses of loss‐of‐function and gain‐of‐function mutant and transgenic lines revealed that the different pathogens require Arabidopsis PSK signalling for cellular reprogramming events that are associated with infection. Our findings indicate that PSK signalling represents a central 'hub' in the host, which is targeted by unrelated pathogens for the establishment of disease.